2019
DOI: 10.1016/j.ekir.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographics of CKD in Canadian Primary Care Practices: A Cross-sectional Study

Abstract: Introduction: Surveillance systems enable optimal care delivery and appropriate resource allocation, yet Canada lacks a dedicated surveillance system for chronic kidney disease (CKD). Using data from the Canadian Primary Care Sentinel Surveillance Network (CPCSSN), a national chronic disease surveillance system, this study describes the geographic, sociodemographic, and clinical variations in CKD prevalence in the Canadian primary care context. Methods: This cross-sectional study included 559,745 adults in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 27 publications
6
40
2
Order By: Relevance
“…This study builds on a previous study 39 that used data from CPCSSN to estimate the prevalence of CKD being managed in primary care practices across Canada. This current work provides an in-depth assessment of the current practice pattern and variations in care for CKD to understand areas of appropriate and inappropriate variation within the context of multimorbidity, patient-centered care, and primary care service delivery to support quality improvement that is most meaningful for patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on a previous study 39 that used data from CPCSSN to estimate the prevalence of CKD being managed in primary care practices across Canada. This current work provides an in-depth assessment of the current practice pattern and variations in care for CKD to understand areas of appropriate and inappropriate variation within the context of multimorbidity, patient-centered care, and primary care service delivery to support quality improvement that is most meaningful for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using data arising from patient care cohorts showed a higher prevalence of stage 3-5 disease (7%-8%). 14,24 Our methodology approximated that of a 2019 study of the prevalence of advanced chronic kidney disease in the general Canadian population, with electronic medical record data extraction from primary care practices. 24 Those authors used only estimated glomerular filtration rate results (no albumin:creatinine ratio), with findings equivalent to ours (prevalence of stage 3-5 disease of 7%).…”
Section: Resultsmentioning
confidence: 99%
“…14,24 Our methodology approximated that of a 2019 study of the prevalence of advanced chronic kidney disease in the general Canadian population, with electronic medical record data extraction from primary care practices. 24 Those authors used only estimated glomerular filtration rate results (no albumin:creatinine ratio), with findings equivalent to ours (prevalence of stage 3-5 disease of 7%). Similarly, in a study using data from health administrative databases from 1980-2005 (before the advent of the electronic medical record) in Saskatchewan, the prevalence of advanced disease was 8%.…”
Section: Resultsmentioning
confidence: 99%
“…The total cost of dialysis is mostly composed of the costs of the treatment itself (including disposables, machines, accommodation, electricity, water and human resources) and the costs of medications, transportation, complications, additional hospital admissions and interventions [331]. Total annual cost of CKD far exceeds $5 billion in Korea [332], $114 billion in US [327] and Canada $40 billion [333]. The prevalence of CKD and ESRD is projected to rise by up to 80% by 2020 due to ageing population and the rising prevalence of diabetes in Australia [334].…”
Section: Renal Failurementioning
confidence: 99%